Broadband Luminescent Dye-Doped Temperature-Tunable Cholesteric Liquid Crystal Laser - Petriashvili, Gia; Maisuradze, Mamuka; Kalandia, Elene; Chubinidze, Ketevan; Chanishvili, Andro; Ponjavidze, Nino; Makharadze, Tamar (Photonics Letters of Poland, 2026)
We have synthesized a luminescent dye that exhibits good solubility in cholesteric liquid crystals and broadband spectral emission. By incorporating this dye into cholesteric liquid crystal and using a nitrogen laser beam as the pumping source, a stable laser emission from the dye-doped cholesteric liquid crystal has been generated. We conducted a temperature-controlled tuning of the laser lines, achieving an extra-wide spectral range of over 172nm, which is the broadest spectral interval so far, using a single luminescent dye. Full Text: PDF References B. Potaniec, M. Zdonczyk, J. Cybinska, "Controlled Synthesis of Luminescent Xanthene Dyes and Use of Ionic Liquid in Thermochromic Reaction", Molecules 27, 3092 (2022). CrossRef L. Gartzia-Rivero, J. Bañuelos, "Special Issue “Design, Synthesis, and Mechanism of Fluorescent and Luminescent Materials”", Int. J. Mol. Sci., 26(17), 8198 (2025). CrossRef J. Mysliwiec, A. Szukalska, A. Szukalski, L. Sznitko, "Liquid crystal lasers: the last decade and the future", Nanophotonics, 10(9), 2309 (2021); CrossRef R. Qu, G. Li, "Overview of Liquid Crystal Biosensors: From Basic Theory to Advanced Applications", Biosensors, 12(4), 1 (2022). CrossRef G. Petriashvili, M.P. De Santo, R.J. Hernandez, R. Barberi, G. Cipparrone, "Mixed emulsion of liquid crystal microresonators: towards white laser systems", Soft Matter 13(36), 6227 (2017). CrossRef A. Chanishvili, K. Chubinidze, G. Petriashvili, N. Ponjavidze, Z. Wardosanidze, T. Zurabishvili, "Spatially Modulated Pumping for Cholesteric Liquid Crystal Lasers", Phot. Lett. Poland, 17(2), 48 (2025); CrossRef K. Dolgaleva, S.K. Wei, S.G. Lukishova, S.H. Chen, K. Schwertz, R.W. Boyd, "Enhanced laser performance of cholesteric liquid crystals doped with oligofluorene dye", J. Opt. Soc. Am. B. 25(9), 1496 (2008); CrossRef M. Uchimura, Y. Watanabe, F. Araoka, J. Watanabe, H. Takezoe, G.-I. Konishi, "Development of Laser Dyes to Realize Low Threshold in Dye-Doped Cholesteric Liquid Crystal Lasers", Adv. Mater. 22, 4473 (2010); CrossRef H. Shirvani Mahdavi, S. Ebrahimi Azandariani, "Effect of combined laser dyes on the efficiency of cholesteric liquid crystal lasers", J. Theor. Appl. Phys. 13(1),7 (2019); CrossRef